SHOPPING MALL: CONSUMPTION, SIMULATION AND SOCIAL CONTROL - Goes, Eda [UNESP] (Univ Lisboa, Fac Letters, Centro Estudos Classicos, 2016)
Shopping mall: consumption, simulation and social control. Consumption has changed in intensity, content and status, making the world conform to it, and associating itself with differentiation processes. We start from this presupposition without ignoring the problems it causes, like alienation. We see shopping malls as strategic to understanding the production of urban spaces in Brazilian middle-sized cities. Our perspective of analysis is that of the everyday, with attention to special practices of different users, and their relations with the producing agents of shopping malls. This implies taking into consideration the symbolic dimensions of consumption (active and collective behavior, system of values, roles of integration and of social control), as well as of shopping malls, supposedly converted into contemporary public spaces. This is directly related with the capacity of shopping malls to habour a strong social control in their interiors, while still producing the sensation of freedom.
Keywords: Shopping mall; consumption; social control; production of urban space